Hydrotropic Solubilization of Lipophilic Drugs for Oral Delivery: The Effects of Urea and Nicotinamide on Carbamazepine Solubility–Permeability Interplay - Beig, Avital; Lindley, David; Miller, Jonathan M.; Agbaria, Riad; Dahan, Arik (Frontiers in Pharmacology, 2016)
Hydrotropy refers to increasing the water solubility of otherwise poorly soluble compound by the presence of small organic molecules. While it can certainly increase the apparent solubility of a lipophilic drug, the effect of hydrotropy on the drugs' permeation through the intestinal membrane has not been studied. The purpose of this work was to investigate the solubility-permeability interplay when using hydrotropic drug solubilization. The concentration-dependent effects of the commonly used hydrotropes urea and nicotinamide, on the solubility and the permeability of the lipophilic antiepileptic drug carbamazepine were studied. Then, the solubility-permeability interplay was mathematically modeled, and was compared to the experimental data. Both hydrotropes allowed significant concentration-dependent carbamazepine solubility increase (up to ~30-fold). A concomitant permeability decrease was evident both in-vitro and in-vivo (~17-fold for nicotinamide and ~9-fold for urea), revealing a solubility-permeability tradeoff when using hydrotropic drug solubilization. A relatively simplified simulation approach based on proportional opposite correlation between the solubility increase and the permeability decrease at a given hydrotrope concentration allowed excellent prediction of the overall solubility-permeability tradeoff. In conclusion, when using hydrotropic drug solubilization it is prudent to not focus solely on solubility, but to account for the permeability as well; achieving optimal solubility-permeability balance may promote the overall goal of the formulation to maximize oral drug exposure.